The Analysis of Changes on The Polish Residential Real Estate Market During The 2020 Pandemic - Robert RUMINSKI (Communications of International Proceedings, 2021)
The literature offers numerous analyses of factors that influence the development of the residential real estate market. A number of theories have been supported by empirical studies and practice providing evidence that macroeconomic conditions and other market-related factors have versatile influence on behavior and decisions made by residential market actors, including their decisions to invest. This multitude of factors and effects they produce require research into current market conditions and short- and long-term forecasts for the market. The analysis and assessment of market conditions and consumer behavior, together with drawing conclusions and producing more or less plausible property market development scenarios, seem to be particularly important in a period of economic disturbances. The article aims to examine the residential real estate market and determine the influence of macro- and microeconomic changes on the development of the market in the light of a unique experience of the 2020 pandemic. The publication puts special emphasis on key parameters and their impact on the domestic housing market. It highlights macroeconomic factors and regulations that influence the housing market, as well as the impact of the pandemic. It also includes a short-term outlook for the period of economic disturbance caused by the pandemic and negative consequences for the housing rental market. The impact of the pandemic on the housing market is multifaceted, and prices on the primary and secondary markets have been revised several times. In a short period, consumer behavior has shown extreme volatility and the economic situation has been unpredictable. In this period of several months, the unknown prospects translated into very difficult conditions for all parties on the market. Due to the domestic and global situation, the economic downturn caused an increase in housing prices in all local market segments. Dramatic increase in the number of infected people during consecutive waves of the pandemic, unfavorable external conditions and the worsening of consumer self-confidence may weaken the demand and strengthen negative pricing trends. Moreover, these problems may be aggravated by obstacles to complete the construction process and proceed with the sales of a record high number of units planned in Poland in 2021-2022.
Keywords: Residential Real Estate Market; Poland; SARS-COV-2 Pandemic